Desempenho produtivo, econômico e características quantitativas das carcaças de cordeiros Santa Inês abatidos com diferentes espessuras de gordura subcutânea - Queiroz, Larissa de Oliveira (2015)
This study objective evaluated the performance and economic results and the quantitative carcass characteristics of lambs Santa Inês breed in feedlot, slaughtered at different subcutaneous fat thickness (SFT) (2.0 or 3.0 or 4.0 mm) by ultrasonography Longissimus dorsi. The experiment was conducted at an experimental farm at the State University of Maringá, Northwest Paraná from March to July 2013. Were used 24 (eight animals per treatment) Santa Inês lambs, not castrated, with approximately 100 days of age and average weight of 22.7 ± 3.75 kg. The lambs were fed once a day with complete pelleted ration, witch availability of 5% of the body weight, calculated for average daily gain of 0.300 kg, and adjusted daily so as to provide approximately 10% remains of. Each 14 days the lams were weighted and subcutaneous fat thickness (SFT) were measured by ultrasonography Longissimus dorsi. The animals slaughter was when the lambs reached the SFT established for its treatment. To evaluate the lambs performance was measured the final body weight, dry matter intake, weight gains and feed conversion. For economic evaluation for slaughter were use the cost with lambs purchase, food and labor to calculate and analyzed the income, expense and profit. Were assessed: body and carcass weights, carcass dressing, carcass and leg compactness index, rib-eye area by measures A (muscle length), B (muscle depth) and C (thickness subcutaneous fat) on Longissimus dorsi and muscle, fat and bone percentages. The final body weight and the total weight gain variables had a statistical difference among treatments, with the higher values to the lambs slaughtered at 4.0 mm subcutaneous fat thickness. However, the lams slaughtered at 3.0 mm SFT showed the better economic results. The carcass dressings at origin, slaughterhouse, commercial and true were changed by the SFT (p <0.05), like as body and carcass weights, the lambs which were slaughtered at 4.0 mm SFT showed higher results than those were slaughtered at 2.0 mm. The body condition and C measure increased as the SFT increase. The SFT increasing is showed witch the percentages of the fat increased, of bone decreased and the muscle did not changed. It is recommended the slaughter of Santa Inês breed sheep at 3.0 mm STF, due to that provided better performance and profit per kilogram of carcass, thus the better economic results, and that provided better results for quantitative carcass characteristics in these conditions of animal husbandry.